2021
DOI: 10.1038/s41598-021-85342-y
|View full text |Cite
|
Sign up to set email alerts
|

Global miRNA/proteomic analyses identify miRNAs at 14q32 and 3p21, which contribute to features of chronic iron-exposed fallopian tube epithelial cells

Abstract: Malignant transformation of fallopian tube secretory epithelial cells (FTSECs) is a key contributing event to the development of high-grade serous ovarian carcinoma (HGSOC). Our recent findings implicate oncogenic transformative events in chronic iron-exposed FTSECs, including increased expression of oncogenic mediators, increased telomerase transcripts, and increased growth/migratory potential. Herein, we extend these studies by implementing an integrated transcriptomic and mass spectrometry-based proteomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 151 publications
2
10
0
Order By: Relevance
“…Using dimethylsulfoxide (DMSO) treated cells as controls, cells were treated with Temsirolimus (TEMS, #50-811-7, Fisher Scientific, Pittsburgh, PA) at a final concentration of 2μM, as described in our prior work ( 17 ). Likewise, as earlier described ( 24 ), 5-Azacytidine (AZA, #S1782, Selleck Chemicals, Houston, TX) was utilized at a final concentration of 1μM while Suberoylanilide hydroxamic acid (SAHA, #S1047, Selleck Chemicals, Houston, TX) was utilized at a final concentration of 50μM. Lysophosphatidic acid (LPA, as a sodium salt in chloroform, #857130C, Avanti Polar Lipids, Alabaster, AL) was utilized at a final dose of 10μM, as previously described ( 17 ).…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…Using dimethylsulfoxide (DMSO) treated cells as controls, cells were treated with Temsirolimus (TEMS, #50-811-7, Fisher Scientific, Pittsburgh, PA) at a final concentration of 2μM, as described in our prior work ( 17 ). Likewise, as earlier described ( 24 ), 5-Azacytidine (AZA, #S1782, Selleck Chemicals, Houston, TX) was utilized at a final concentration of 1μM while Suberoylanilide hydroxamic acid (SAHA, #S1047, Selleck Chemicals, Houston, TX) was utilized at a final concentration of 50μM. Lysophosphatidic acid (LPA, as a sodium salt in chloroform, #857130C, Avanti Polar Lipids, Alabaster, AL) was utilized at a final dose of 10μM, as previously described ( 17 ).…”
Section: Methodssupporting
confidence: 70%
“…As previously described ( 24 ), RNA was isolated from cells using the miRVana isolation kit (#AM1561, Ambion, NY) or the RNeasy mini kit (QIAGEN, Valencia, CA) following manufacturer’s instructions. RNA was quantified using NanoDrop 1000 (Fisher Scientific, Pittsburg, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Iron 22 BioMed Research International metabolism has been reported to be regulated by miRNAs, which have been demonstrated to posttranscriptionally regulate the expression of genes associated with iron acquisition, iron export, iron storage, iron utilization, and coordi-nation of systemic iron homeostasis [43][44][45]. We found that some dysregulated miRNAs in IPAH patients regulate iron metabolism in other biological circumstances [44,[46][47][48]; given that both iron metabolism disorders and miRNA dysregulation are important regulators of IPAH development, we hypothesized that there is crosstalk between them in IPAH patients and then constructed a DRmiRNA-DEIMRG regulatory network and identified 12 tIMRGs. In addition, we identified 10 hub genes in DEIMRGs that are highly associated with other proteins through the construction of PPI networks.…”
Section: Discussionmentioning
confidence: 78%
“…For example, human bronchial epithelial cells exposed to tobacco particles were tested for malignant transformation, confirming the effect of tobacco particulates on lung carcinogenesis 73 . The chronic iron exposure‐induced ovarian serous carcinoma was demonstrated by continuous exposure of fallopian tube secretory epithelial cells to ferric ammonium citrate 74 . This suggests that in vitro cellular carcinogenic test is an important method to study the carcinogenic effects of toxicants.…”
Section: Disscussionmentioning
confidence: 85%
“…73 The chronic iron exposure-induced ovarian serous carcinoma was demonstrated by continuous exposure of fallopian tube secretory epithelial cells to ferric ammonium citrate. 74 This suggests that in vitro cellular carcinogenic test is an important method to study the carcinogenic effects of toxicants. Therefore, this study explored the carcinogenic effect of MC-LR, a possible human carcinogen in the environment, by a malignant transformation test.…”
Section: Construction Of Mc-lr-induced Malignant Transformation Model...mentioning
confidence: 99%